Radio frequency magnetic field mapping of a 3 Tesla birdcage coil: experimental and theoretical dependence on sample properties. - Alecci, M; Collins, C; Smith, M; Jezzard, P (2001)
The RF B(1) distribution was studied, theoretically and experimentally, in phantoms and in the head of volunteers using a 3 T MRI system equipped with a birdcage coil. Agreement between numerical simulation and experiment demonstrates that B(1) distortion at high field can be explained with 3D full-Maxwell calculations. It was found that the B(1) distribution in the transverse plane is strongly dependent on the dielectric properties of the sample. We show that this is a consequence of RF penetration effects combined with RF standing wave effects. In contrast, along the birdcage coil z-axis the B(1) distribution is determined mainly by the coil geometry. In the transverse plane, the region of B(1) uniformity (within 10% of the maximum) was 15 cm with oil, 6 cm with distilled water, 11 cm with saline, and 10 cm in the head. Along z the B(1) uniformity was 9 cm with phantoms and 7 cm in the head.